Pengaruh ukuran perusahaan dan leverage terhadap nilai perusahaan dengan profitabilitas sebagai variabel moderasi - Siwi Nur Khotimah; Rita Indah Mustikowati; Ati Retna Sari (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2020)
This study aims to examine and explain the effect of company size and leverage on firm value with profitability as a moderating variable in Real Estate and Property companies listed on the Indonesia Stock Exchange in the period 2016-2018. This type of research is explanatory research, testing classical assumptions, and analyzed using a moderated regression analysis, and using the t test. The number of samples is 32 companies, and the sampling method used is purposive sampling. This research variable consists of company size and leverage as an independent variable, company value as the dependent variable, and profitability as a moderating variable. The analysis showed that partially company size and leverage had no significant effect on firm value, profitability had a negative effect on firm value and profitability weakened the effect of company size on firm value and profitability strengthened the effect of leverage on firm value. In this study, it can provide implications for a company to consider factors of company size, leverage, and profitability, and can also be used as a reference by other companies in business strategy, understand aspects of the industry they are involved in, and pay more attention to the development of the environment that can affect the company's business so that it can increase the value of the company.